PENGEMBANGAN MEDIA ALAT HITUNG PEMBAGIAN BERBASIS KARTON DAN SEDOTAN UNTUK MENINGKATKAN PEMAHAMAN KONSEP PEMBAGIAN SISWA KELAS III SDN SALEM 01 KABUPATEN BREBES - Galih Januarahmana; Tri Suminar (STKIP Subang, 2026)
This study aims to develop a division counting tool made from cardboard and straws as a mathematics learning medium for third-grade elementary school students. The background of this research is based on students’ low understanding of the concept of division and the limited use of concrete learning media in classroom instruction. The research method employed was Research and Development (R&D) using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were 31 third-grade students of SDN Salem 01, Brebes Regency, consisting of a single class without a comparison group. Data collection techniques included observation, interviews, questionnaires, and learning achievement tests. The results showed that the developed media achieved a very high validity level based on expert judgments. Furthermore, the field testing results indicated a significant improvement in students’ understanding of division concepts after using the developed media. Therefore, the cardboard and straw-based division counting tool is feasible and effective as an alternative mathematics learning medium in elementary schools.